Why does the Iranian National Program of Screening Newborns for G6PD Enzyme Deficiency Miss a Large Number of Affected Infants?. (1st February 2014) - Kosaryan, Mehrnoush; Mahdavi, Mohammad Reza; Jalali, Hossein; Roshan, Payam
<x xml:space="preserve">Abstract</x> Purpose: G6PD enzyme deficiency is one of the most prevalent genetic disorders worldwide and it has high incidence rate in Northern provinces of Iran. It was observed that national neonatal screening for G6PD enzyme deficiency fails to detect all affected infants. In order to clarify the cause, this study has been done in Thalassemia Research Center, Sari, Iran. Materials and Methods: This was a diagnostic study. The newborns with parents of Mazandarani origin were enrolled. Cord blood from the placental side was collected and used for decolorization test, quantitative enzyme assay (QEA) and DNA study. A heel-prick sample collected on day 3–5 after birth was used for fluorescent spot test (FST). In male cases, QEA was considered as the gold standard. For females, DNA study was considered as the gold standard. Based on QEA test results, neonates with <20% and 20–60% of mean normal enzyme activity were considered as total deficient and partial deficient, respectively. Results: A total of 365 neonates (52.3% females and 47.7% males) were studied. According to FST, 13 male newborns had G6PD deficiency. No deficient female was detected. Decolorization test diagnosed 18 male and one female as G6PD deficient newborns. QEA diagnosed 19 males and 28 females with G6PD enzyme deficiency (26 partial, 2 total deficient cases). DNA analysis detected 14 males as hemizygote and 34 females as heterozygote. Conclusion: FST does not have the required sensitivity for newborn screening and QEA is recommended as the preferred method.